2021
DOI: 10.48550/arxiv.2103.14053
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantum-inspired identification of complex cellular automata

Abstract: Elementary cellular automata (ECA) present iconic examples of complex systems. Though described only by one-dimensional strings of binary cells evolving according to nearest-neighbour update rules, certain ECA rules manifest complex dynamics capable of universal computation. Yet, the classification of precisely which rules exhibit complex behaviour remains a significant challenge. Here we approach this question using tools from quantum stochastic modelling, where quantum statistical memory -the memory required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Comparatively, it was shown that Cq → C q if L ≥ R and when the length of the stochastic process goes to infinity, N → ∞. The quantum inference protocol was recently used to demonstrate the relative complexity of elementary cellular automate [46]. The cardinality of A implies that the quantum inference protocol produces a maximum of A L quantum memory states for L-length consecutive pasts.…”
Section: Framework a Stochastic Processes And Modelsmentioning
confidence: 99%
“…Comparatively, it was shown that Cq → C q if L ≥ R and when the length of the stochastic process goes to infinity, N → ∞. The quantum inference protocol was recently used to demonstrate the relative complexity of elementary cellular automate [46]. The cardinality of A implies that the quantum inference protocol produces a maximum of A L quantum memory states for L-length consecutive pasts.…”
Section: Framework a Stochastic Processes And Modelsmentioning
confidence: 99%